2016
DOI: 10.1242/dev.127647
|View full text |Cite
|
Sign up to set email alerts
|

The ADP-ribose polymerase Tankyrase regulates adult intestinal stem cell proliferation during homeostasis in Drosophila

Abstract: Wnt/β-catenin signaling controls intestinal stem cell (ISC) proliferation, and is aberrantly activated in colorectal cancer. Inhibitors of the ADP-ribose polymerase Tankyrase (Tnks) have become lead therapeutic candidates for Wnt-driven cancers, following the recent discovery that Tnks targets Axin, a negative regulator of Wnt signaling, for proteolysis. Initial reports indicated that Tnks is important for Wnt pathway activation in cultured human cell lines. However, the requirement for Tnks in physiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 69 publications
3
71
0
Order By: Relevance
“…Indeed, small molecule inhibitor studies have indicated that Tnks is important for the Wnt-dependent regeneration of fins following injury in adult fish (Chen et al 2009;Huang et al 2009). Moreover, our recent work has revealed that regulation of Axin by Drosophila Tnks is required for Wingless target gene activation and the Wingless-dependent control of intestinal stem cell proliferation in the adult midgut Wang et al 2016). Importantly, in the midgut, Tnks is essential for target gene activation in regions where the Wingless pathway is activated at relatively low levels, but dispensable at high levels , suggesting a critical role for Tnks in the amplification of signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, small molecule inhibitor studies have indicated that Tnks is important for the Wnt-dependent regeneration of fins following injury in adult fish (Chen et al 2009;Huang et al 2009). Moreover, our recent work has revealed that regulation of Axin by Drosophila Tnks is required for Wingless target gene activation and the Wingless-dependent control of intestinal stem cell proliferation in the adult midgut Wang et al 2016). Importantly, in the midgut, Tnks is essential for target gene activation in regions where the Wingless pathway is activated at relatively low levels, but dispensable at high levels , suggesting a critical role for Tnks in the amplification of signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Redundancy in Axin degradation pathways would provide a compensatory fail-safe mechanism to prevent an increase in Axin above its threshold and the resultant inhibition of signaling. Functional redundancy in Axin degradation pathways may also explain why no defects in Wnt-dependent embryonic development were observed upon disruption of fish or fly Tnks (Huang et al 2009;Feng et al 2014;Wang et al 2016). Nonetheless, the high degree of sequence conservation present in Tnks homologs suggests that Tnks loss cannot be fully compensated by other pathways in all in vivo contexts.…”
Section: Discussionmentioning
confidence: 99%
“…3, Figs 4f and 5). Furthermore, Drosophila Tnks is essential for Wg target gene activation in the adult intestine, and exclusively within regions of the gradient where Wg is present at relatively low concentration 49,64 . Thus, the context-specific roles of Tnks observed in different model organisms may reflect the mechanisms described herein, which reveal that the Wntinduced association of Axin with LRP6 occurs even in the absence of Axin ADP-ribosylation, but is markedly enhanced in its presence.…”
Section: Discussionmentioning
confidence: 99%
“…The Wingless pathway is also involved in adult tissue self-renewal in Drosophila (Lin et al, 2008). Genetic depletion of proteins in the Wingless pathway, such as Tcf, arr, dsh and pygo, leads to inhibition of Wingless signaling activation which in turn causes over-proliferation of stem cells in the Drosophila midgut (Kramp et al, 2002;Wang et al, 2016a and2016b;Tian et al, 2016). However, inactivation of Wnt signaling in the small intestine of mice decreases the proliferative potential of stem cells (Fevr et al, 2007;Korinek et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The principal components of this complex are adenomatous polyposis coli (APC), mice are overall normal; however, double knock-out of Tnks1/2 causes early embryonic lethality, which indicates their redundancy in mouse development (Hsiao et al, 2006;Chiang et al, 2008). On the other hand, inactivation of the single Drosophila Tnks gene produces viable flies that have slightly increased Axin levels but no overt defects (Wang et al, 2016a and2016b;Feng et al, 2014;Yang et al, 2016;Tian et al, 2016). Therefore, the exact physiological function of TNKS and Iduna-mediated regulation of Wnt-signaling remains to be determined.…”
Section: Introductionmentioning
confidence: 99%